METODE LOGIKA FUZZY UNTUK PEMECAHAN LINEAR PROGRAMMING 2 VARIABEL - Cucu Tohir; Yusuf Sumaryana (JUTEKIN (Jurnal Teknik Informatika), 2014)
Fuzzy logic (Fuzzy Logic) is a problem solving methodology with ten - thousands of applications stored in the controller and processing information in adopting human assessment conducted on a truth. Fuzzy logic provides a simple way to describe the definitive conclusions from the information that is ambiguous, vague - vague or imprecise. To some extent resembles a fuzzy logic decision making in humans with the ability to work from the data that is interpreted and seek appropriate solutions. In most digital systems, TRUE or FALSE truth assessed (0 and 1). Whereas in human judgment there is a vacillation between right and wrong. Fuzzy logic is basically worth a lot of logic (multivalued logic) that can define values between the conventional circumstances such as yes or no, right or wrong, black or white, and so on. Fuzzy reasoning provides a way to understand the performance of the system by assessing the input and output of the system of observation.Keyword: Logic Fuzzy, Linear, Programming